Assessment of quality of life among HIV infected people on antiretroviral therapy in a tertiary hospital, Karnataka - Sreeranga, Anjan; Pavithra, P.; Meundi, Anand D. (International Journal Of Community Medicine And Public Health, 2021)
Background: With the availability of highly effective antiretroviral treatment, HIV is transforming into a chronic condition, whose management is now experiencing problems of other chronic diseases, where quality of life (QOL) has become an important component of overall assessment of health care and management. This study was conducted with the objective of assessing the QOL and factors influencing it in HIV infected people on antiretroviral therapy (ART). Methods: A cross-sectional study was conducted at district ART center, Hassan. Purposive sampling was used to identify 148 HIV infected people on antiretroviral therapy, who were interviewed using a pretested questionnaire, assessing QOL with the World Health Organization (WHOQOL) HIV‑BREF. Results: The average age of the study population was 37.69 years. Majority of them were males 54.7% compared to 45.3% of females. Most of them resided in rural areas (87.8%). The educational status of the subjects was poor with 33.8% of them being illiterates. The mean score was highest for spirituality and social relationships domain and least for psychological domain. Age, education and socioeconomic status did not have any influence on the QOL. There was significant difference between QOL scores and clinical stages. Individuals in stage I and II had better scores compared to stage 3 and 4. QOL scores decreased with decreasing CD4 count. Conclusions: Our findings suggest that patient-reported measures of health status and related concepts may help provide a feasible, reliable and valid method to assess the impact of HIV/AIDS improve patient outcomes.